Comparative Analysis of Students’ Applying Skills in Science Based on TIMSS 2019: Evidence from Indonesia, Laos, and Cyprus - Janah Janah; Vongsone Simmavong; Sherzad Sherzad (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to analyze and compare students’ ability to apply scientific concepts for problem-solving based on the TIMSS 2019 cognitive domain of applying in Indonesia, Laos, and Cyprus. Methodology: The study employed a quantitative comparative research design using secondary data from the TIMSS 2019 International Database released by the International Association for the Evaluation of Educational Achievement (IEA). Data were obtained from official international reports and analyzed descriptively using comparative statistical techniques to examine differences in the applying domain of science achievement. Main Findings: The results show that Indonesia achieved a low level of performance in the applying domain of science, while Laos demonstrated slightly higher but still limited performance. Cyprus achieved a moderate level of applying skills. The findings indicate significant disparities in students’ ability to apply scientific concepts across the three countries, reflecting differences in instructional emphasis and learning orientation. Novelty/Originality of this study: This study provides a focused cross-national comparison of the applying cognitive domain in science using TIMSS 2019 data, which is rarely examined explicitly. The findings contribute new insights into how the application of scientific concepts varies across educational contexts and offer empirical evidence to support curriculum and instructional reforms aimed at strengthening problem-solving skills in science education.